Perioperative Management of Extended-Release Buprenorphine: A Narrative Review and Case Series. Issue 1 (January 2023) - Hickey, Thomas R.; Meeks, Thomas; Oxentine, Heather; Park, Dong Chan; Abelleira, Audrey; Edens, Ellen; Gordon, Adam J.; Acampora, Gregory
Background: Perioperative management of formulations of buprenorphine used for the treatment of opioid use disorder and/or pain are common clinical challenges. Care strategies are increasingly recommending continuation of buprenorphine while administering multimodal analgesia including full agonist opioids. While this "simultaneous strategy" is relatively simple for the shorter-acting sublingual buprenorphine formulation, best practices are needed for the increasingly prescribed extended-release buprenorphine (ER-buprenorphine). To our knowledge there are no prospective data to guide perioperative management of patients on ER-buprenorphine. Herein we provide a narrative review, report on the perioperative experiences of a series of patients maintained on ER-buprenorphine, and propose recommendations for perioperative ER-buprenorphine management based on best evidence, clinical experience, and our judgments. Cases: Here we present clinical data describing the perioperative experiences of patients maintained on extended-release buprenorphine who recently underwent a variety of surgeries ranging from outpatient inguinal hernia repair to multiple inpatient surgeries for source control in sepsis, at different medical centers throughout the United States. These patients were identified via an email solicitation to substance use disorder treatment providers throughout a nationwide healthcare system, requesting cases of patients maintained on extended-release buprenorphine who had recently undergone surgery. We report here on all of the cases received. Discussion: Extrapolating from these and recently published case reports, we describe an approach to perioperative management of extended-release buprenorphine.